A NOVEL STRATEGY FOR SLIM‐FLOOR FIRE PROTECTION. Issue 1 (26th April 2023) - Romero, M.L.; Albero, V.; Espinós, A.; Serra, E.; Hospitaler, A.; Pons, D.
Abstract: This paper presents a novel slim‐floor configuration which consist of an I‐section steel profile welded to a wider bottom steel plate with an insulation layer of 5mm thick placed in between the two. The insulation layer is made up of a flexible and non‐combustible material, which protects the I‐section profile from the temperature rise through its bottom surface. Besides, this insulation layer remains protected from external agents with no need of maintenance because it is placed in the cavity created on purpose between the bottom plate and the lower flange of the steel profile thank to the weld between them. This new slim‐floor configuration is currently right‐protected by the Spanish Office of Patents and Trademarks with the reference number P201930438 and has been tested in the Universitat Politècnica de Valencia testing facilities to assess its thermal behaviour in fire. Specifically, the specimen was tested using an electric furnace where the slim‐floor is placed at the top surface. Therefore, the composite beam is exposed to the heat source only from the bottom surface, as it is the case in real fire scenarios. Moreover, the experimental campaign includes also a common slim‐floor specimen, without the insulation layer, in order to compare their thermal behaviour. The steel parts used in all the test specimens were grade S355, having a nominal yield strength of 355 MPa, the nominal compressive strength (cylindrical) of the cast in‐situ concrete was 30 MPa and the precast concrete hollow core slabs were manufactured with 45 MPa nominal compressive strength (cylindrical). In turn, the embedded reinforcing bars were grade S500, with 500 MPa nominal yield strength. The first experimental results have shown that the temperature gap between the bottom steel plate and the lower flange of the steel profile can reach up to 200°C. This impressive thermal gap delays the temperature rise along the I‐section steel profile which produces a significant improvement on the composite section fire resistant time, up to 90 or 120 minutes. Additionally, it should be highlighted that the observed improvement on the cross‐section thermal behaviour has been achieved using a novel configuration which no need maintenance in contrast with the common external protection systems using intumescent coating or other fireproofing materials.